Adaptive Counseling System: Inovasi Pengembangan Layanan Konseling Digital Berbasis Metode Agile - Edoardo Yanuar Putra; Farida Ardiani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Counseling services are a form of psychological support and educational tool that play an important role in student development in the school environment. The main objective of these services is to help students develop strong, independent characters that are ready to face future challenges in academic, social, and emotional aspects. However, in many schools, including SMAN 1 Demak, the counseling service system used is still conventional, such as manual recording and limited communication. This causes the counseling process to be less effective, less conducive, and time-consuming. These problems require the use of information technology in the form of digitizing counseling services. This study aims to develop a digital counseling service system based on the Agile method, which allows the system development process to be carried out iteratively and adaptively to user needs. The system was developed using the agile development method in the form of a mobile application using the Kotlin programming language. Blackbox testing was also carried out to ensure that the Adaptive Counseling system was running properly, and User Acceptance Testing (UAT) was used to ensure that the system design was feasible for use. This system can improve the work efficiency of guidance counselors, accelerate access to student data, and create a more interactive and structured counseling space. This can be proven from the Black Box results, which show that 100% of the system's functionality runs according to the design. With the implementation of this digital system, counseling services at SMAN 1 Demak can run more optimally, modernly, and in accordance with the needs of the times.